Effects of nitrogen, phosphorus, EDTA and sodium chloride on biomass and lipid accumulation of Chaetomorpha aerea - Satpati, Gour Gopal; Pal, Ruma (Current Botany, 2020)
The increase of total lipid and fatty acids production was studied under different nutrient stress conditions using the macroalga, Chaetomorpha aerea. The effects of nitrogen, phosphorus, ethylene diamine tetra-acetate and sodium chloride on the growth and lipid accumulation were systematically investigated in laboratory conditions. The biomass was harvested at different stages of cultivation and assessed. The maximum changes of growth and lipid accumulation were observed in the exponential phase at different cultural conditions. The two-fold increase of total lipid was found in the order of 28.27±0.04 % (at 0.1 g/L nitrogen) > 27.30±0.37 % (at 0.5 g/L of phosphorus) > 25.86±0.77 % (at 0.05 g/L of EDTA)> 24.37±0.04 % (at 0.05 g/L NaCl) on 8th day of cultivation. The fatty acids were identified and quantified by gas chromatography mass spectrometry (GC-MS). The alga produces significantly high amount of monounsaturated fatty acid (MUFA) and saturated fatty acids (SFA) than the polyunsaturated fatty acids (PUFA) in different cultural conditions. The elevated levels of C16:1, C18:1 and C20:1 was identified under nitrate, phosphate and salt stress conditions, which are more suitable for biodiesel production.